Research on cancer diagnosis in Malaysia: current status. - Looi, L.M.; Zubaidah, Z.; Cheah, P.L.; Cheong, S.K.; Gudum, H.R.; Iekhsan, O.; Ikram, S.I.; Jamal, R.; Mak, J.W.; Othman, N.H.; Puteri, J.N.; Rosline, H.; et al. (College of Pathologists, Academy of Medicine Malaysia, 2004)
Cancer is a major morbidity and mortality concern in Malaysia. Based on National Cancer Registry data, the Malaysian population is estimated to bear a cancer burden of about 40,000 new cases per year, and a cumulative lifetime risk of about 1:4. Cancer research in Malaysia has to consider needs relevant to our population, and resources constraints. Hence, funding bodies prioritise cancers of high prevalence, unique to our community and posing specific clinical problems. Cancer diagnosis is crucial to cancer management. While cancer diagnosis research largely aims at improvements in diagnostic information towards more appropriate therapy, it also impacts upon policy development and other areas of cancer management. The scope of cancer diagnosis upon which this paper is based, and their possible impact on other R&D areas, has been broadly categorized into: (1) identification of aetiological agents and their linkages to the development of precancer and cancer (impact on policy development, cancer prevention and treatment), (2) cancer biology and pathogenesis (impact on cancer prevention, treatment strategies and product development), (3) improvements in accuracy, sensitivity and specificity in cancer detection, monitoring and classification (impact on technology development) and (4) prognostic and predictive parameters (impact on treatment strategies). This paper is based on data collected by the Working Group on Cancer Diagnosis Research for the First National Conference on Cancer Research Coordination in April 2004. Data was collated from the databases of Institutions/Universities where the authors are employed, the Ministry of Science, Technology and Innovation (MOSTI) and targeted survey feedback from key cancer researchers. Under the 7th Malaysia Plan, 76 cancer projects were funded through the Intensified Research in Priority Areas (IRPA) scheme of MOSTI, amounting to almost RM15 million of grant money. 47(61.8%) of these projects were substantially in cancer diagnosis, accounting for 65.6% (RM 9.7 million) of cancer project funds. The 8th Malaysia Plan saw a change in research strategy. The IRPA agency fielded several top-down projects which encouraged a multicentre and multidisciplinary approach. This resulted in larger funding per project i.e. RM32 million for 49 projects. There was also a surge of interest in drug development and natural products. Because of this shift in direction, cancer diagnosis projects constituted only 51% of IRPA-funded cancer projects. Nonetheless funding for cancer diagnosis research has exceeded that of the 7th Malaysia Plan, being RM12.5 million by March 2004. The majority of such research is carried out at the Universities, engaging a large number of young scientists and postgraduate students (51 MSc and 21 PhD). A lot of research findings presented at scientific meetings have not yet been published and there is a glaring shortage of patents and commercialization of research findings (such as creation of test kits). Because diagnosis is very much a part of clinical practice, many researchers felt satisfied and confident that their work will be translated into practice and will significantly improve diagnostic services in Malaysia. National guidelines and consensus development on at least three malignancies i.e. breast cancer, oral cancer and lymphoma, have substantial basis in local R&D work. Problems encountered in research included (1) insufficient funding to realize research objectives, (2) lack of local expertise (most research assistants are inexperienced BSc graduates with no or minimal research experience), (3) inadequate technical support from vendors during equipment failure, (4) inexperienced Institutional development units to assist in product development, (5) lack of venture capital for commercialization of findings, and (6) inadequate incentives to undertake research. Researchers pointed out that plans to promote research should include the establishment of (1) regional and national cancer tissue banks, (2) a National Cancer Research Institute, (3) a dedicated cancer research fund, (4) a registry of cancer researchers, (5) national research coordinators, (6) improved coverage by the National Cancer Registry, (7) more international collaboration, (8) a better career structure for researchers, (9) improved Institutional support for product realization, and (10) better recognition for cancer researchers.